PICTORIAL STORY TOWARD THE STUDENTS’ ABILITY IN READING NARRATIVE TEXT IN SMP NEGERI 7 PADANGSIDIMPUAN - Rambe, Nana Ronawan (LP2M IAIN Ambon, 2021)
bstract The factors that affect students' ability to read narrative text are motivation, teacher quality, infrastructure, teaching and teaching materials methods that use narrative text reading strategies. Class VIII students of SMP Negeri 7 Padangsidimpuan have low understanding in reading narrative text. This study aims to see the effect of using pictorial stories on students' ability to read narrative texts in class VIII of SMP Negeri 7 Padangsidimpuan. This research uses quantitative methods. Based on the results of the test analysis, it was found that the average number of students' ability to read narrative text before using the story was 79.5 and it was included in the